Product design requirements for Kelulut hive - Suhaimi, Abu Dzar; Azhar, Nur Aida Elyna; Amir, Adibah; Syed Shaharuddin, Sharifah Imihezri; Mohd. Zaki, Syazwani (2021)
Kelulut is also referred to as stingless bees that can only be found in a tropical and subtropical climates. In the natural environment, kelulut typically builds their hive in hollow trunks and underground cavities. However, cutting down the trees and removing the colony has a detrimental effect on the forest ecosystem as kelulut are good pollinators. As an alternative, kelulut have been farmed in various locations in Malaysia. In these farms, the hives for the kelulut are commonly constructed vertically with three main components. These components consist of the entrance, brood chamber, and honey box.